Current trends and policies of energy consumption and CO2 emission from the largest Asian economies. (2018) - Sarkar, Md. Sujahangir Kabir; Begum, Rawshan Ara; Sadeka, Sumaiya; Pereira, Joy Jacqueline
This article presents the current trends of energy consumption and CO2 emission as well as their relationship for the five largest Asian economies i.e., People's Republic of China (China), Japan, India, Republic of Korea (South Korea) and Indonesia using the time series data from 1991 to 2014. The total energy consumption has increased by 3.62 times from 1991 to 2014 in China where India, Korea and Indonesia have faced more than double of their energy consumption during that time. However, total CO2 emission in China, India, Korea and Indonesia was increased by 3.5, 2.81, 2.25 and 3.14 times respectively from 1991 to 2014. All the countries except Japan are facing increasing trends of energy consumption and CO2 emission while positive and significant relationship have found between them for all the countries. Thus, the implementation of current policies and emission reduction target of these five countries are presented in this paper.